Bi-parental mucus provisioning in the scale-eating cichlid Perissodus microlepis (Cichlidae). (23rd October 2019) - Satoh, Shun; Awata, Satoshi; Tanaka, Hirokazu; Jordan, Lyndon A; Kakuda, Umi; Hori, Michio; Kohda, Masanori
Abstract: Although parental care is known to occur in a wide range of teleost fishes, postnatal provisioning of nutrition has been documented rarely. Here, we describe a novel example of bi-parental care in a teleost, i.e. mucus-provisioning behaviour in the scale-eating cichlid Perissodus microlepis endemic to Lake Tanganyika. Field observations revealed that young guarded by their parents frequently glanced towards the body surface of both parents. Furthermore, analyses of stomach contents of the young found the presence of ingested mucus, confirming that the young feed on the mucus secretions of their parents. The frequency of glancing behaviour increased with size of the young up to 13 mm in standard length, but then declined with further growth. Additionally, the frequency of glancing of young towards their parents was higher when the frequency of foraging on plankton was lower. Underwater cage experiments revealed a higher rate of growth in the young kept in direct contact with their parents than in those not allowed direct contact. We conclude that glancing behaviour in young P. microlepis is a form of direct parental nourishment that confers growth benefits to the young when food abundance is low.